2000
DOI: 10.1089/jop.2000.16.429
|View full text |Cite
|
Sign up to set email alerts
|

Role of Catalase in Pre- and Postjunctional Responses of Mammalian Irides to Hydrogen Peroxide

Abstract: In the present study, we examined the effect of inhibition of catalase with 3-aminotriazole (3-AT) on hydrogen peroxide (H2O2)-induced enhancement of sympathetic neurotransmission in bovine irides and on the inhibitory effect of this oxidant on norepinephrine (NE) release from human irides, in vitro. Furthermore, we investigated the effect of 3-AT on H2O2-induced attenuation of contractile responses to carbachol in the bovine isolated irides. Isolated mammalian irides were prepared for studies of [3H]NE releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The enzyme CAT which is involved in the metabolism of H 2 O 2 has also been linked to neurotransmission regulation by peroxides in ocular tissues. Matutte et al showed that the inhibition of catalase unmasked an excitatory action of H 2 O 2 on evoked NE release and an inhibitory effect on muscarinic receptor-induced contraction of iris smooth muscle (Matutte et al, 2000). These studies establish that inhibiting peroxide metabolism causes both sympathetic nerves and smooth muscles of the anterior uvea to be more susceptible to the harmful effects of H 2 O 2 .…”
Section: Role Of Oxidant-derived Metabolites In Pathogenesis Of Eye Dmentioning
confidence: 99%
“…The enzyme CAT which is involved in the metabolism of H 2 O 2 has also been linked to neurotransmission regulation by peroxides in ocular tissues. Matutte et al showed that the inhibition of catalase unmasked an excitatory action of H 2 O 2 on evoked NE release and an inhibitory effect on muscarinic receptor-induced contraction of iris smooth muscle (Matutte et al, 2000). These studies establish that inhibiting peroxide metabolism causes both sympathetic nerves and smooth muscles of the anterior uvea to be more susceptible to the harmful effects of H 2 O 2 .…”
Section: Role Of Oxidant-derived Metabolites In Pathogenesis Of Eye Dmentioning
confidence: 99%